In vitro study of the prebiotic xylooligosaccharide (XOS) on the growth of Bifidobacterium spp and Lactobacillus spp. (17th November 2015) - Li, Zhaoping; Summanen, Paula H.; Komoriya, Tomoe; Finegold, Sydney M.
Abstract: We recently demonstrated that XOS increased the counts of Bifidobacterium in vivo without increasing Lactobacillus in healthy adults. In the current study, we evaluated the effect of XOS on the growth of 35 Bifidobacterium and 29 Lactobacillus strains in in vitro conditions. Bacteria were identified by 16S rRNA sequence analysis. The growth stimulation was determined by agar dilution technique on plates containing two-fold serial dilutions of XOS (100–0.1 mg/ml). The growth of 86% of Bifidobacterium strains was stimulated at 1.56 mg/ml XOS and 100% at 6.25 mg/ml XOS. The growth of 38% of Lactobacillus strains was stimulated at 1.56 mg/ml XOS and 62% at 6.25 mg/ml XOS; 31% of Lactobacillus were not stimulated by XOS. Our results further suggest that XOS may be beneficial in stimulating intestinal Bifidobacterium without having much effect on Lactobacillus . The potential role for XOS in managing obesity should be investigated further.